2012
DOI: 10.1016/j.celrep.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

SGTA Recognizes a Noncanonical Ubiquitin-like Domain in the Bag6-Ubl4A-Trc35 Complex to Promote Endoplasmic Reticulum-Associated Degradation

Abstract: Elimination of aberrantly folded polypeptides from the endoplasmic reticulum (ER) by the ER-associated degradation (ERAD) system promotes cell survival under stress conditions. This quality control mechanism requires movement of misfolded proteins across the ER membrane for targeting to the cytosolic proteasome, a process facilitated by a ‘holdase’ complex, consisting of Bag6 and the cofactors Ubl4A, Trc35. This multiprotein complex also participates in several other protein quality control processes. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
150
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(164 citation statements)
references
References 61 publications
9
150
1
Order By: Relevance
“…Because SGTA impacts the virus-Hsc70 interaction, we sought to determine whether SGTA's ability to associate with Hsc70 via SGTA's central TPR domain (Fig. 4A) (32-34), as well as SGTA's N-terminal domain, which mediates homodimerization and the recruitment cellular adapters, including the Ubl4A-Tric35-Bag6 complex (33)(34)(35)(36), is important during ER extraction and cytosol arrival of the virus. Since SGTA's C-terminal domain is limited to substrate binding (31,37,38) and unlikely to control Hsc70's function, we did not characterize this domain in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Because SGTA impacts the virus-Hsc70 interaction, we sought to determine whether SGTA's ability to associate with Hsc70 via SGTA's central TPR domain (Fig. 4A) (32-34), as well as SGTA's N-terminal domain, which mediates homodimerization and the recruitment cellular adapters, including the Ubl4A-Tric35-Bag6 complex (33)(34)(35)(36), is important during ER extraction and cytosol arrival of the virus. Since SGTA's C-terminal domain is limited to substrate binding (31,37,38) and unlikely to control Hsc70's function, we did not characterize this domain in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The TPR domain of Sgt2 is also involved in the homeostasis of other proteins (54,55). A recent study revealed that Sgt2 interacts with two key chaperones (Ssa1 and Hsp104) involved in prion pathogenesis and affects prion formation in yeast (56).…”
Section: Discussionmentioning
confidence: 99%
“…The Bag6 min fragment used in the study does not contain the Bag6 substrate-binding domain ( therefore, the Bag6 complex can promote the handoff of substrate from SGTA to TRC40 without Bag6 engaging the substrate directly. SGTA binds the Bag6 complex via the UBL domain of Ubl4A; consequently, the Bag6-dependent handoff should require this interaction (24,25). To test this hypothesis, the mutants hSGTA(C38A) and Ubl4A(L43A) were generated; previously, the equivalent mutations in yeast were shown to disrupt the homologous interaction (25).…”
Section: The Bag6 Min Complex Is An Independent Module That Facilitatmentioning
confidence: 99%
“…In yeast, these two proteins form a heterotetramer that regulates the handoff of the TA protein from the cochaperone small, glutamine-rich, tetratricopeptide repeat protein 2 (Sgt2) [small glutamine-rich tetratricopeptide repeat-containing protein (SGTA) in mammals] to the delivery factor Get3 (TRC40 in mammals) (19)(20)(21)(22). It is expected that the mammalian homologs, along with Bag6, play a similar role (23)(24)(25)(26)(27). Bag6 also interacts with other proteins such as apoptosisinducing factor, glycoprotein 78 (gp78), regulatory particle 5, and brother of regulator of imprinted sites (BORIS) (16,(27)(28)(29)(30)(31)(32) and can homo-oligomerize, increasing the level of complexity (30).…”
mentioning
confidence: 99%